TATAG DE PENYAWO - Usman . (Saraswati)
Tatag De Penyawo dance work is work that pours stylist experience. Tatag de Penyawo comes from Tidung. Tatag means losing, which in this work is meant losing the Dayak identity, while De Penyawo mean that in the sense of the heart's deepest. Anxiety on the identity of questionable and even questioning his own identity, as is customary to be lost because of religion stylist is believed to be the theme of this work. Anxiety within the stylist to maintain and preserve the tradition is so strong Dayak, Dayak tradition itself while the conflict with Islamic values. This dance is danced in groups, with 9 dancers. Properties used are Hudoq We, Hudoq-Kublo, and loincloth. It rests on the dance dance Hudoq us. Presentation mode used symbolic representational. This dance work can be classified as a type of dramatic dance, which means that the idea is communicated full allure, dynamic, cause tension and possible conflict between the people involved in her or with others. This dance work processes involving several parties that help, both in the search and in the creation of works of reference as a medium for the stylist to socialize and interact with their surroundings. Through the work of this dance, stylists feel emotional or  spiritual  closeness  to  the  tradition  and  culture  of  the  Dayak  ancestors.  Form  of gratitude and love for the cultural traditions of the ancestors are expected to be realized through the work of this final. Keywords: Tatag De Penyawo, Identity, Hudoq